Symmetric solutions for hybrid fractional differential equations - Jessada Tariboon (2018)
© 2017 by Eudoxus Press, LLC, All rights reserved. In this paper we introduce a new class of symmetric functions and study the existence of symmetric solutions for hybrid Caputo fractional differential equations. A fixed point theorem in Banach algebra for two operators is used. An example is presented to illustrate our result.